TERT-Promoter Mutational Status in Glioblastoma – Is There an Association With Amino Acid Uptake on Dynamic 18F-FET PET? - Unterrainer, Marcus; Ruf, Viktoria; von Rohr, Katharina; Suchorska, Bogdana; Mittlmeier, Lena Maria; Beyer, Leonie; Brendel, Matthias; Wenter, Vera; Kunz, Wolfgang G.; Bartenstein, Peter; Herms, Jochen; Niyazi, Maximilian; et al. (Frontiers in Oncology, 2021)
The mutation of the ‘telomerase reverse transcriptase gene promoter’ (TERTp) has been identified as an important factor for individual prognostication and tumorigenesis and will be implemented in upcoming glioma classifications. Uptake characteristics on dynamic 18F-FET PET have been shown to serve as additional imaging biomarker for prognosis. However, data on the correlation of TERTp-mutational status and amino acid uptake on dynamic 18F-FET PET are missing. Therefore, we aimed to analyze whether static and dynamic 18F-FET PET parameters are associated with the TERTp-mutational status in de-novo IDH-wildtype glioblastoma and whether a TERTp-mutation can be predicted by dynamic 18F-FET PET. Patients with de-novo IDH-wildtype glioblastoma, WHO grade IV, available TERTp-mutational status and dynamic 18F-FET PET scan prior to any therapy were included. Here, the established clinical parameters maximal and mean tumor-to-background-ratio (TBRmax/TBRmean), the biological-tumour-volume (BTV) and minimal-time-to-peak (TTPmin) on dynamic PET were analysed and correlated with the TERTp-mutational status. One hundred IDH-wildtype glioblastoma patients were evaluated; 85/100 of the analyzed tumors showed a TERTp-mutation (C228T or C250T), 15/100 were classified as TERTp-wildtype. None of the static PET parameters was associated with the TERTp-mutational status (median TBRmax 3.41 vs. 3.32 (p=0.362), TBRmean 2.09 vs. 2.02 (p=0.349) and BTV 26.1 vs. 22.4 ml (p=0.377)). Also, the dynamic PET parameter TTPmin did not differ in both groups (12.5 vs. 12.5 min, p=0.411). Within the TERTp-mutant subgroups (i.e. C228T (n=23) & C250T (n=62)), the median TBRmax (3.33 vs. 3.69, p=0.095), TBRmean (2.08 vs. 2.09, p=0.352), BTV (25.4 vs. 30.0 ml, p=0.130) and TTPmin (12.5 vs. 12.5 min, p=0.190) were comparable, too. Uptake characteristics on dynamic 18F-FET PET are not associated with the TERTp-mutational status in glioblastoma. However, as both, dynamic 18F-FET PET parameters as well as the TERTp-mutation status are well-known prognostic biomarkers in glioblastoma, future studies should investigate the complementary and independent prognostic value of both factors in order to further stratify patients into risk groups.